EVALUASI SPT TAHUNAN ELEKTRONIK - Elsie S. Kasim; Titin F. Nur (Program Pendidikan Vokasi Universitas Indonesia, 2016)
Evaluation of services of Electronic Annual Tax Return is conducted to determine the quality of services ofElectronic Annual Tax Return. This is done by using the five Service Quality (SERVQUAL) dimensionswhich are tangibles, realibility, responsiveness, assurance and empathy. The result of the research and analysis ofEvaluation of services of Electronic Annual Tax Return concluded that Taxpayers are satisfied with the qualityof Electronic Annual Tax Return. Advices given to the djponline.pajak.go.id websites is it should be moreattentive to the needs of the Taxpayers. Djponline.pajak.go.id websites should not only pay attention to thefunctions but also increased trust amoung Taxpayers toward djponline.pajak.go.id websites.Keywords: Evaluation of services, Electronic Annual Tax Return, Service Quality